Development and validation of the treatment expectation scale for patients with liver cancer - Xiaoyi Yang; Ruijun Yang; Yang Xu; Shuang Zang (Archives of Medical Science)
Introduction Liver cancer is one of the most common tumors in the world. Patients with liver cancer usually face substantial physical, psychological, and social burdens, which has created a great demand and expectation to ease the burden in all aspects. This study aimed to develop and validate the Treatment Expectation Scale for patients with Liver Cancer (TES-LC).